2013
DOI: 10.1371/journal.pone.0070965
|View full text |Cite
|
Sign up to set email alerts
|

Aurora B but Not Rho/MLCK Signaling Is Required for Localization of Diphosphorylated Myosin II Regulatory Light Chain to the Midzone in Cytokinesis

Abstract: Non-muscle myosin II is stimulated by monophosphorylation of its regulatory light chain (MRLC) at Ser19 (1P-MRLC). MRLC diphosphorylation at Thr18/Ser19 (2P-MRLC) further enhances the ATPase activity of myosin II. Phosphorylated MRLCs localize to the contractile ring and regulate cytokinesis as subunits of activated myosin II. Recently, we reported that 2P-MRLC, but not 1P-MRLC, localizes to the midzone independently of myosin II heavy chain during cytokinesis in cultured mammalian cells. However, the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 68 publications
(86 reference statements)
2
3
0
Order By: Relevance
“…On the other hand, both pRLC and ppRLC localization were decreased at the equatorial cortex (Figure S1C). As a control, we found ROCK inhibition caused a global reduction in pRLC, ppRLC, and MIIA localization at the cortex during cytokinesis, in agreement with previous reports (Figure S1D) (Kosako et al, 2000;Dean et al, 2005;Watanabe et al, 2007;Kondo et al, 2013). Taken together, our data suggest that ROCK is involved in MII recruitment, while MLCK is involved in MII turnover at the cortex To test whether the increase in membrane blebbing was also observed during interphase, we turned to filamin-deficient M2 cells that constitutively bleb during interphase (Charras et al, 2006).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, both pRLC and ppRLC localization were decreased at the equatorial cortex (Figure S1C). As a control, we found ROCK inhibition caused a global reduction in pRLC, ppRLC, and MIIA localization at the cortex during cytokinesis, in agreement with previous reports (Figure S1D) (Kosako et al, 2000;Dean et al, 2005;Watanabe et al, 2007;Kondo et al, 2013). Taken together, our data suggest that ROCK is involved in MII recruitment, while MLCK is involved in MII turnover at the cortex To test whether the increase in membrane blebbing was also observed during interphase, we turned to filamin-deficient M2 cells that constitutively bleb during interphase (Charras et al, 2006).…”
Section: Resultssupporting
confidence: 93%
“…This data shows that MLCK inhibition results in a decrease in pRLC, but not ppRLC localization. In contrast, we found that ROCK inhibition resulted in a significant loss of ppRLC from the cortex during metaphase, which is consistent with what has been previously shown during cytokinesis (Kondo et al, 2013) (Figure S1A).…”
Section: Resultssupporting
confidence: 92%
“…RACGAP1 also interferes with the mitotic spindle apparatus, therefore being involved in the regulation of cell proliferation . So far, aurora kinase B (AURKB) has been reported to interact with RACGAP1 in solid cancers . For AURKA, previous evidence has suggested only an indirect link via AURKA‐mediated STAT3 activation and RACGAP1‐dependent STAT signaling .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, RhoA is required for AMR assembly in mammalian cells ( Figure 4B; Basant and Glotzer, 2018;Verma et al, 2019). The chromosomal passenger complex (CPC), including its components Aurora B and survivin, appears to regulate IIB localization during the abscission stage ( Figure 4B; Kondo et al, 2013;Babkoff et al, 2019). Similar to Myo1 in budding yeast (Fang et al, 2010), the central region of the IIA tail (residues 834-1,632) is required for its localization to the division site (Figure 1), but its tethering factor at the division site remains unknown (Beach and Egelhoff, 2009).…”
Section: Localization and Dynamics Of The Nm-iia -Iib And -Iic Durimentioning
confidence: 99%